Determinan Kinerja Pegawai Dinas Kesehatan Kabupaten Tapanuli Tengah - Roiman Sinaga; Meutia Meutia; Fatia Fatimah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to analyze the effect of training, competence and individual characteristics on employee performance in the health office of Central Tapanuli Regency. This type of research is a quantitative study with a saturated sample method, amounting to 65 employees at the Central Tapanuli District Health Office. The results showed that partially training and competence had no significant effect on employee performance in the Health Office of Central Tapanuli Regency. While the characteristic variables have a significant effect on employee performance in the Health Office of Central Tapanuli Regency. Simultaneously training, competence and individual characteristics have a significant effect on employee performance in the Health Office of Central Tapanuli District.